Diretrizes para a conciliação no superendividamento: pesquisa e intervenção para contribuir com o procedimento - PALÁCIOS, Luciana Silva Rassy (Universidade Federal do Pará, 2023)
Brazilian Federal Law no. 14.181/2021 amended the Brazilian Consumer Protection Code to improve credit discipline and legislate about prevention and treatment of over-indebtedness, lauching a special conciliation procedure. This law prescribes a self-composition procedure with all creditors and the consumer through a plan of payment that can repactuate debts jointly, as long as keepes existential minimum for the person. The basic hypothesis is that conciliation in over-indebtedness has specific characteristics if compared to the ordinary conciliation procedure, that must be observed to preserve the over-indebtedness treatment policy. The research is built of theoretical and practical parts, and focus on answering the question of how to present the particularities of the conciliation procedure in over-indebtedness through systematization of processes and techniques, in order to help conciliators face burocracy. In order to achieve that, the following objectives were set: a) identify the particular characteristics of conciliation in over-indebtedness procedure in relation to the common conciliation; b) establish practical guidelines to present these particularities and offer training to the public agent responsible do conduct the conciliation procedure. An academic article was elaborated focusing on answering the question about the particularities of the special conciliation procedure in over-indebtedness in comparison to the common conciliation. Also, the product of intervention, classified as a proposal of processes and techniques, is structured as a manual, in which basic legal literature and practices applied to the conciliation in over-indebtedness procedure is organized, aiming to gather technical knowledge and ease the activity routine. Research will also highlight communication techniques and skills in conciliation, adapting them to the special conciliation procedure in over-indebtedness. The research products have qualitative and exploratory nature, and are applied in order to collaborate as a specific base to present the characteristics of conciliation in over-indebtedness, so as to train people to this practice with quality and justice.